Psychopathology history, diagnosis, and empirical foundations - Craighead, W. Edward; Miklowitz, David Jay 1957-; Craighead, Linda W. (Hoboken Wiley, 2017)
"A modern take on adult disorders, incorporating context, research, and more Psychopathology provides unique, state-of-the-art coverage of adult psychopathology as categorical, evidence-based, and continuously evolving. Comprehensive coverage features a detailed examination of DSM disorders, including description, epidemiology, prevalence, consequences, neurobiological and translational research, treatment, and more, with each chapter written by an experts in the field. Mapped to the DSM-5, each chapter includes clinical case examples that illustrate how psychopathology and assessment influence treatment. This new third edition has been updated to align with the latest thinking on alcohol and substance use disorders, sleep-wake disorders, and personality disorders. Students will delve into the DSM system's limitations and strengths, and they will gain deeper insight into the historical context in which today's diagnoses are made. Advancing research continues to broaden the boundaries of psychopathology beyond traditional lines, revealing its complexity while simultaneously deepening our understanding of these disorders and how to treat them. This book goes beyond DSM descriptions to provide a comprehensive look at the whole disorder, from assessment through treatment and beyond. Review DSM-5 classifications matched with illustrative case examples Learn the neurobiological and genetic factors related to each disorder Understand related behavioral, social, cognitive, and emotional effects Delve into translational research, assessment methodologies, and treatment Contributions from specialists in each disorder provide exceptional insight into all aspects of theory and clinical care. Psychopathology helps students see the whole disorder--and the whole patient"--Provided by publisher.
"Presents an overview of the issues and methodologies of conducting assessments for the various forms of psychopathology"--Provided by publisher.
Machine generated contents note: preface acknowledgments list of contributors -- Chapter 1. Diagnosis: conceptual issues and controversies / Scott O. Lilienfeld, Sarah Francis Smith, and Ashley L. Watts -- Chapter 2. Social anxiety disorder / Deborah Roth Ledley, Brigette A. Erwin, Amanda S. Morrison, and Richard G. Heimberg -- Chapter 3. Panic disorder / Joanna J. Arch, Alex Kirk, and Michelle G. Craske -- Chapter 4. Generalized anxiety / Disorder Karen Rowa, Stephanie Waechter, Heather K. Hood, and Martin M. Antony -- Chapter 5. Obsessive compulsive and related disorders / Jonathan S. Abramowitz and Shannon M. Blakey -- Chapter 6. Posttraumatic stress disorder / Patricia A. Resick, Candice M. Monson, and Stefanie T. LoSavio -- Chapter 7. Depressive disorders / W. Edward Craighead, Daniel N. Klein, Charles F. Gillespie, Lorie A. Ritschel, and Katherine E. Phillips -- Chapter 8. Bipolar disorders / David J. Miklowitz and Sheri L. Johnson -- Chapter 9. Sleep-wake disorders / Lu Dong, Jennifer C. Kanady, and Allison G. Harvey / Chapter 10. Schizophrenia and the psychosis spectrum / Arthur T. Ryan, Hanan D. Trotman, Vijay A. Mittal, Kevin D. Tessner, and Elaine F. Walker -- Chapter 11. Substance-related disorders / Lara A. Ray, Kelly E. Courtney, ReJoyce Green, and Guadalupe A. Bacio -- Chapter 12 Eating disorders / Linda W. Craighead, Margaret A. Martinez, Kelly L. Klump, James Lock, and Nina Kirz -- Chapter 13. Sexual dysfunctions / Cindy M. Meston and Amelia M. Stanton -- Chapter 14. Borderline personality disorder / Jill M. Hooley and Sara R. Masland -- Chapter 15. Psychopathy / Jennifer E. Vitale and Joseph P. Newman.
Revised edition of Psychopathology, [2013].
Includes bibliographical references (pages 640-650) and index.
Keywords: Psychology, Pathological